STATE BUDGET DEFICIT: STRUCTURAL CAUSES, MACROECONOMIC IMPLICATIONS AND INTEGRATED SOLUTIONS - Umirov Sherzod Bakriddinovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
The state budget is considered the center of the financial system, and the balance in it is the main criterion for the economic security of the country. However, in modern world practice, almost all states operate in conditions of a certain level of budget deficit (deficit). A budget deficit is a state in which government spending exceeds its income .